'Enabling dissent': Contesting austerity and right populism in Toronto, Canada. (March 2016) - Thomas, Mark; Tufts, Steven
Following the 2008 financial crisis, austerity measures have been introduced in many national contexts to reorganise public sector work and redesign labour laws and labour policies. At the same time, right-populist discourses and movements have arisen in ways that give both legitimacy and voice to the politics of austerity. Toronto, Canada, provides a world-renowned case of populist experimentation at the metropolitan scale, as the actions of Mayor Rob Ford typified this nexus of austerity and populism. Set in the context of Ford's term as Mayor of Toronto (2010–2014), this article asks how the combined rise of austerity and right populism creates both new challenges and new opportunities for public sector labour in urban spaces. We argue that public sector unions are central in both the making and unmaking of populist austerity and identify potential trajectories for organised labour in the face of the continuation of austerity-driven politics.